Argentinean Real Exchange Rate 1900-2006: Testing Purchasing Power Parity Theory - del Bianco, Marco (Estudios de Economía, 2016)
This paper tests the Purchasing Power Parity Theory of Exchange Rates dealingwith Argentinean data for the period 1900-2006. This is equivalent to testing ifthe Real Exchange Rate is a stationary variable or if its components (the nominalexchange rate and the relative prices) are cointegrated. Since most works studydeveloped countries or developing countries but with short span data, this paperaims to fill a gap in the wide PPP literature by studding a developing country witha long-run approach. This country is particularly interesting since during 20thcentury “Argentine economic performance tells a story of decline unparalleledin modern times” (Taylor 1992). The downfall of this once developed countryhas probably affected the behavior of its RER and the validity of PPP. To checkthis, we use a wide set of econometric techniques and found that the PPP theoryis not verified in Argentina, since its RER appears as a non-stationary variable,and there is no evidence of cointegration between the nominal exchange rateand the relative prices. In particular, the Argentinean RER appears to betrend-stationary under structural breaks with a continuous real depreciationof the Argentinean currency, especially in the first half of XX century, which isconsistent with theories that relate the secular impoverishment of a country withthe depreciation of its RER, as the Balassa-Samuelson effect.